Nutritional analysis of Sesamum Radiatum seeds - Umi Raihanah Muhamad Sam (2019)
Presence of valuable chemical compositions in plant has been attracts researcher and consumer to use it for research and healing treatment. Sesamum radiatum is an annual herbaceous plant which is commonly distribute at the tropical and subtropical areas in Asia but native to Africa .Sesamum radiatum is family Pedaliaceae. Its common name is Benniseed and Black Benniseed. The purpose of this study was to determine moisture, ash, fat, protein, carbohydrates and food energy content from the Sesamum radiatum seeds using various analytical and biochemical method. This study also was conducted to determine mineral content (Ca, Mg, K, Na, Cu) from Sesamum radiatum seeds using atomic absorption spectrophotometer (AAS). Thus, studies has revealed Sesamum radiatum content 4.24% moisture, 6.27% ash, 43.48% fat, 20.60% protein, 25.41% carbohydrates and 577.36 Kcal/g food energy content. The seeds also were found to be good sources of minerals where Potassium (111.8 mg/L) Calcium (175.1 mg/L), Magnesium (57.35 mg/L), Sodium (3.043 mg/L) and Copper (0.346 mg/L). This plant has show high nutritive value which can be exploited as a good source of food and supplements.